Investigating the association between HIV and AIDS and polygamy among practising polygamists in Kwazulu-Natal, North Coast area - Nyathikazi, Thobekile Jacobeth Lungile (Stellenbosch : Stellenbosch University, 2013)
Thesis (MPhil)--Stellenbosch University, 2013.